Pengaruh Penyemprotan Monokalium Fosfat dan Pemangkasan Pucuk terhadap Pertumbuhan dan Hasil Produksi Tanaman Cabai Rawit (Capsicum frustescens L.) pada Hidroponik Sistem Dutch Bucket - Setyadi, Farhad Dwi; Fanata, Wahyu Indra Duwi (Jember University Press, 2024)
Cayenne pepper plant (Capsicum frustences L.) is a plant that is synonymous with its spicy taste, so consumption needs are increasing. However, production of cayenne pepper plants has decreased due to a decrease in land conversion and climate influences. Application of hydroponic dutch bucket system and monopotassium phosphate (MKP) spraying as well as shoot pruning techniques at certain times to increase production. This research aims to determine the effect of MKP spraying and shoot pruning on the growth and production of cayenne pepper plants using the dutch bucket hydroponic system. The experimental design used two factorsthree test. The first factor is variation in concentration of MKP administration, with 3 levels. The second factor is the pruning time with 3 levels so that there are 27 experimental units. The data is then analyzed and evaluated using analysis of Variance (ANOVA). Each observed variable is analyzed separately and significant differences between average values are based on tests Duncan Multiple Range Test (DMRT) with a confidence level of 95%. The results show for the stem diameter variable, the monopotassium phosphate spraying treatment gave very significantly different results and shoot pruning gave significantly different results.The combination of monopotassium phosphate spraying treatment with a dose of 4 g/liter and a shoot pruning time of 21 days after planting (M3N2) gave the highest results for the variables of stem diameter, number of flowers to fruit, number of fruit, and fruit weight.